Influence of deposition time on the electrocatalytic activities of core-shell Co(OH)2/NiS/NF electrode. (March 2021) - Yang, Yuying; Meng, Haixia; Zhang, Yan; Li, Zhimin; Zhang, Ziyu; Zhongai, Hu
Graphical abstract: Highlights: Heterogeneous core-shell Co(OH)2 /NiS/NF electrocatalyst is synthesised. Co(OH)2 /NiS presents 3D nanoarrays structure. Co(OH)2 /NiS/NF exhibits excellent electrocatalytic performance for the HER. Co(OH)2 /NiS/NF can serve as an efficient catalyst for overall water splitting. Abstract: Developing low-cost and high-effective bifunctional electrocatalysts is an efficient way to reduce the energy consumption of hydrogen production via electrochemical water splitting. Herein, 3D heterogeneous core-shell Co(OH)2 /NiS nanoarrays supported on nickel foam (Co(OH)2 /NiS/NF) were prepared by an easy stepwise hydrothermal strategy and the next electrochemical deposition process. The as-prepared Co(OH)2 /NiS/NF composite was used as an effective electrocatalyst for overall water splitting. A series of electrocatalyst with different shell thickness were gained by controlling the time of the electrochemical deposition. The optimized Co(OH)2 /NiS/NF-400 s electrocatalyst presented good catalytic activity for the HER in 1.0 M KOH, the overpotentials is 69 mV at a current density of 10 mA cm −2 and the Tafel slope is 125 mV dec −1 . Furthermore, the alkaline electrolyzer used Co(OH)2 /NiS/NF-400 s as both the cathode and anode catalyst acquired low cell voltage of 1.53 V at 10 mA cm −2 and showed excellent electrochemistry stability. The results illustrated that the as-prepared heterogeneous core-shell electrocatalyst can be used as an efficient catalyst for overall water splitting.